Electricity-structure-fluid coupled modelling and experiment of underwater flexible structure with partially distributed macro fiber composites. (February 2022) - Lou, Junqiang; Chen, Tehuan; Yang, Yiling; Xu, Chao; Chen, Hairong; Ma, Jianqiang; Cui, Yuguo; Li, Guoping
Dynamic oscillating behavior of the flexible structure immerged in viscous fluids has attracted growing attention and been widely used in various practical applications. A general electricity-structure-fluid coupled model for the forced dynamic responses of a cantilever immersed in fluids, with partially distributed macro fiber composite, is proposed in this paper. Based on the classical Euler–Bernoulli beam theory, the first mass-normalized mode shape of the cantilever with partially bonded macro fiber composite is determined using assumed mode method. The attachment of the macro fiber composite actuators stiffens the macro fiber composite-bonded portion of the cantilever. The established mode shape matches perfectly with experimental results. Considering the macro fiber composite actuator as a set of representative elements connected in parallel, the internally actuation moment provided by the macro fiber composite actuators is obtained. The hydrodynamic load caused by the surrounding fluids, decomposed into the added mass and hydrodynamic damping parts, is also added to the theoretical model in the frequency-domain form. The predicted in-air and underwater dynamic behaviors of the flexible beam are consistent with the experimental results at different auction levels. Thus, the obtained general electricity-structure-fluid coupled model can be used to predict the forced dynamic responses of flexible structure with partially bonded actuators immersed in fluids.